2011
DOI: 10.1182/blood.v118.21.4340.4340
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Positive Red Blood Cell Antibody Screen with Inconclusive Antibody Identification

Abstract: 4340 Introduction: The routine blood type and screen involves screening for unexpected antibodies, in addition to checking the ABO group and RH type. Most of these antibodies are IgM type, also known as nuisance antibodies. They are thought not to have much clinical significance. A positive antibody screen can sometimes be associated with inconclusive antibody identification. An inconclusive antibody screen is defined as test reactive for gel screen (which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Type and screen (T&S) is an essential protocol and diagnostic procedure for patients in order to detect any unexpected antibodies, as well as checking the blood group and type (Gupta et al, 2011). Type refers to phenotype typing including ABO groups and Rh types, and screen refers to the unexpected antibodies testing that might cause a delay in the crossmatching of blood and increased risk of alloimmunization or transfusion reaction (Seheult et al, 2017; Yazer, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Type and screen (T&S) is an essential protocol and diagnostic procedure for patients in order to detect any unexpected antibodies, as well as checking the blood group and type (Gupta et al, 2011). Type refers to phenotype typing including ABO groups and Rh types, and screen refers to the unexpected antibodies testing that might cause a delay in the crossmatching of blood and increased risk of alloimmunization or transfusion reaction (Seheult et al, 2017; Yazer, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…According to Gupta et al 16 , 23.2% (n=16/69) of patients with positive antibody screening, but inconclusive antibody identification was identified as having a definite antibody when retested at a later date. Nevertheless, 48.0% (n=33/69) of these patients had negative antibody screening.…”
Section: Discussionmentioning
confidence: 99%
“…The situation in which a positive for gel test of antibody screening, but no defined pattern on antibody identification panel was classified as inconclusive antibody screening. On the other hand, positive antibody screening may also be associated with inconclusive antibody identification 16 .A gel test in which dextran acrylamide gel placed in microtubes containing anti-IgG is reliable, accurate, and sensitive for the detection and identification of blood group antibodies 17,18 . Indeed,Weisbach et al 19 found that the high-sensitivity of the microcolumn gel system produced higher falsepositive ratesthan the conventional tube system.…”
Section: Discussionmentioning
confidence: 99%